The acoustics of the Mekor Haim Synagogue, Portugal - António P. Carvalho (2011)
This paper focuses on synagogues and in the acoustic characterization to the main worship area of the 1938 Mekor Haim synagogue (Oporto, Portugal), the largest in volume in the Iberian Peninsula. Reverberation Time (RT), Rapid Speech Transmission Index (RASTI) and the equivalent noise level of background traffic noise, were measured on the floor where the Torah is read (and where men have their seats), and on the top floor where women have their seats. The analyses of the results are done as a comparison with values found in other studies regarding Catholic churches and mosques with similar volume. The main results found are: average RT (5001k Hz) of 4.6 s, average RASTI of 0.37 and 0.31 on the mens and womens floors respectively, average sound pressure level of background noise of 54/59 dB on men/womens floors (36/37 dBA) and NC-31/32 or NR-32/33 at the men/womens floors. Suggestions for improving the acoustics of this synagogue are presented that can make the RT values to decrease to about 2 s with the corrections taking place only at its dome.